Development of Standard Components of SMAN 1 Lingsar Library Based on National Library Standards - Iqbal, Muhammad; Hardiansyah, Hardiansyah; Kurniawati, Wiwien (UNDIKMA, 2025)
School library management with conventional systems is time-consuming and ineffective. This study aims to develop a development model for SMAN 1 Lingsar library standard components based on SNP. The method used is research and development with observation and FGD as data collection techniques. The results include the addition of book collections from student grants, improvement of facilities and infrastructure, optimization of services with barcode applications, technical training, funding from the West Lombok Regency Library, and development through book review competitions and automatic inventory. Suggestions are provided for implementing this model to meet school library standards.